The international criminal responsibility for war crimes committed by the British troops in Iraq 2003- 2008 within the framework of the international criminal court (ICC) - Hameed, Haider Abdulrazaq (IJARD, 2018)
In 2003, the United States of America established an international alliance to wage war against Iraq.Britain was the main strategic ally of the US.In this war, the British troops committed war crimes during the invasion and after the occupation in Iraq between 2003 to 2008, but the problem is: How to prove the responsibility of these forces for war crimes in Iraq? The aim of this paper is to shed light the most important war crimes within the jurisdiction of the ICC so that victims can prosecute these forces for these crimes committed against them, as well as to support and activate a deterrent mechanism by punishing the perpetrators of these crimes in order to stop the crimes from happening in the future.The methodology adopted in this paper is a doctrinal legal research, this methodology has been chosen to examine the issues involved and clarify ambiguities and place them in a logical and coherent structure.As a result of war crimes committed against Iraqi victims, the British forces bear full international criminal responsibility for these crimes under Article 8 of the ICC Statute.